PANGGUNG GANDA: PRESENTASI DIRI ANGGOTA GYM DI RUANG FISIK DAN RUANG MEDIA SOSIAL - Muhammad Luthfi Fadhil Fadhil; Michael Jibrael Rorong (LPPM Universitas Putera Batam, 2026)
This study examines the phenomenon of double staging in the self-presentation practices of gym members, which takes place in physical spaces and continues into social media spaces. The fitness activities carried out by StrongGym members are not only interpreted as exercise routines, but also as a means of building and displaying self-identity through the body, appearance, and accompanying communication activities. The gym space functions as a front stage where individuals display their self-image directly, while Instagram Stories becomes an extension of the stage that allows individuals to manage and curate their visual self- representation. The results of the study show that self-representation in physical and digital spaces are interconnected in shaping the social identity of gym members. The experience of exercising at the gym is the main basis for selecting content to be displayed on Instagram Stories, but digital representations tend to show the best moments that have gone through a selection process. In addition, communication activities that take place in both spaces have different characteristics, where face-to-face communication in the gym is direct and interactive, while communication in the digital space is symbolic and representational through visuals, text, and audience responses. These findings confirm that the self-presentation practices of gym members reflect Erving Goffman's concept of dramaturgy, in which individuals consciously manage their impressions in front of different audiences in different contexts.